Integrasi Kebijakan Hukum dan Nilai-nilai Kearifan Lokal dalam Mewujudkan Pelayanan Dasar yang Optimal - Ngaisah, Siti; Mufidah, Nuruz Zakiyatul; Sumaryanto, A. Djoko (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2025)
This study explores the integration of national legal policies with local wisdom values as a strategic approach to realizing optimal basic public services and ensuring social justice in Indonesia. It highlights challenges in policy implementation, including centralistic legal frameworks that often overlook indigenous cultural values, leading to social resistance and conflicts.. The research emphasizes the importance of harmonizing national laws with local wisdom through adaptive, pluralistic legal mechanisms and participatory governance models. Case studies demonstrate how local legal products, customary dispute resolutions, and community-based governance strengthen social cohesion and legitimacy of law. The paper further recommends enhancing legal literacy, capacity building for local actors, and multi-stakeholder collaboration involving government, customary institutions, academia, and civil society to foster inclusive, responsive, and sustainable legal frameworks. Innovative public service models rooted in local cultural practices are shown to improve accountability, participation, and resilience. This integrative approach not only protects constitutional rights and indigenous heritage but also supports environmentally sustainable development and equitable public service delivery, contributing to national cohesion and governance effectiveness.